Development and Mechanical Characterization of Sustainable Bioplastics from Water Hyacinth Cellulose and Sweet Corn Cob Starch - Fiqi Putra Pratama Aryanto; Sintha Soraya Santi; Aulia Putri Damayanti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study aims to investigate the effect of water hyacinth (Eichhornia crassipes) cellulose and sweet corn cob (Zea mays) starch on the characteristics of bioplastics. The increasing environmental issues caused by non-biodegradable plastics have encouraged the development of eco-friendly alternatives such as bioplastics derived from renewable biomass. There are two JIS standards referred to in this study. First, JIS K7113 is used to measure the tensile strength and elongation of bioplastics. Second, JIS K7209 is used to measure water absorption. By meeting both standards, bioplastics made from water hyacinth and sweet corn cob are proven to have quality equivalent to conventional plastics according to Japanese industrial standards. .In this research, bioplastics were prepared using varying cellulose-to-starch ratios (0.2–1.0 g) and glycerol as a plasticizer (0.5–1.5 mL). The films were produced through gelatinization at 70°C followed by drying. The resulting bioplastics were evaluated based on tensile strength, elongation, and water absorption. The results showed that increasing cellulose content improved tensile strength, reaching a maximum of 9.51 MPa at a 1:1 ratio with 0.5 mL glycerol. Although the exact value is not stated in the abstract, based on similar research data, the maximum water absorption value can reach approximately 54.93%. This highest value occurs in the composition with the highest glycerol content (1.5 mL) because glycerol is hydrophilic (easily attracts water). The higher the glycerol concentration, the greater the bioplastic's ability to absorb water. Conversely, higher glycerol concentrations decreased tensile strength but increased elongation, with the highest elongation value reaching 50.09%. Water absorption increased with higher glycerol content due to its hydrophilic nature. Overall, the produced bioplastics met the Japanese Industrial Standard (JIS) requirements, indicating their potential as environmentally friendly alternatives to conventional plastics. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 14: Life Below Water SDG 15: Life on Land